Part-time employment can be a life-time setback for earnings: a study of British women 1975 - 2001 - Sara Connolly; Mary Gregory (Institute for the Study of Labor (IZA), 2007)
Two particular features of the position of women in the British labour market are the extensive role of part-time work and the large part-time pay penalty. Part-time work features most prominently when women are in their 30s, the peak childcare years and, particularly for more educated women, a crucial period for career building. This makes it essential to understand its impact on women's subsequent earnings trajectories. We find that the wage return to part-time experience is low negligible in lower skill occupations. Even more important channels contributing to the pay disadvantage of women working part-time are job changing, particularly when this involves occupational downgrading. Downgrading can lead to a permanent pay disadvantage for women following a spell in part-time work.
Keywords: 330; Female employment; part-time work; occupation; earnings trajectories; life-cycle; downgrade; over-qualification; Frauenerwerbstätigkeit; Teilzeitarbeit; Qualifikation; Bildungsertrag; Lohndifferenzierung; Lebenszyklus; Panel; Schätzung; Großbritannien